Population Genomics of a Cosmopolitan Weed Provides Insights Into Its Local Adaptation and Recent Demographic History - Marilia Souza Lucas; Christoph Rosche; Isabell Hensen; Stefan G. Michalski; Dávid U. Nagy; Diana Gamba; Renske E. Onstein; Karime Abidkulova; Mohammad Al‐Gharaibeh; Ali A. Al‐Namazi; Sirwan Babaei; Fernando Bastida; et al. (Molecular Ecology, 2026)
Invasive plant species present a growing ecological and economic challenge, and often adapt rapidly to their novel environments through complex demographic and evolutionary processes. Invasion genomics offers powerful tools to disentangle these processes, but most studies rely on geographically narrow sampling across native and non‐native ranges. Erigeron canadensis is a cosmopolitan weed native to North America that has successfully invaded diverse climates worldwide. We used double‐digest restriction site‐associated DNA sequencing (ddRADseq) to investigate the genetic diversity and structure of 280 E. canadensis populations across the Northern Hemisphere. We found that native and non‐native populations maintained comparable genetic diversity. Population structure analyses revealed four genetic clusters that were mainly differentiated along latitudinal and aridity gradients. However, one cluster was strongly overrepresented in the non‐native compared to the native range. In the native range, genetic differentiation was shaped by spatial and environmental gradients, while in non‐native regions human‐mediated dispersal and repeated introductions disrupted environmentally driven genetic structure. Migration network analyses revealed limited intercontinental connectivity and a possible role of long‐distance dispersal in within‐range expansions. Genomic offset analyses showed that genotype‐environment mismatches in non‐native populations associated with reduced growth and reproduction. Together, our results indicate that the invasion dynamics of E. canadensis were driven by multiple introductions, population admixture, and lineage sorting, while some genotypes contributed disproportionately to the spread of this invader. The presence of apparent maladaptation suggests that even long‐established invaders may still be evolving in response to their novel environment, raising concerns about potential future expansions.

Sustainable conversion of acid mine drainage sludge into high-quality iron-based pigments through thermal processing - Alexandra Zamfir; Aurelia Meghea; Ovidiu Cristian Oprea; Maria Mihaly (Process Safety and Environmental Protection, 2025)

Brain opportunistic infections and tumors in people living with HIV — still a challenge in efficient antiretroviral therapy era - Cristiana Oprea; Irina Ianache; Sorina Vasile; Cristiana Costescu; Gratiela Tardei; Maria Nica; Anya Umlauf; Cristian Achim (Journal of NeuroVirology, 2023)

Phenotypic plasticity masks range‐wide genetic differentiation for vegetative but not reproductive traits in a short‐lived plant - Jesus Villellas; Johan Ehrlén; Elizabeth E. Crone; Anna Mária Csergő; Maria B. Garcia; Anna‐Liisa Laine; Deborah A. Roach; Roberto Salguero‐Gómez; Glenda M. Wardle; Dylan Z. Childs; Bret D. Elderd; Alain Finn; et al. (Ecology Letters, 2021)
Genetic differentiation and phenotypic plasticity jointly shape intraspecific trait variation, but their roles differ among traits. In short‐lived plants, reproductive traits may be more genetically determined due to their impact on fitness, whereas vegetative traits may show higher plasticity to buffer short‐term perturbations. Combining a multi‐treatment greenhouse experiment with observational field data throughout the range of a widespread short‐lived herb, Plantago lanceolata , we (1) disentangled genetic and plastic responses of functional traits to a set of environmental drivers and (2) assessed how genetic differentiation and plasticity shape observational trait–environment relationships. Reproductive traits showed distinct genetic differentiation that largely determined observational patterns, but only when correcting traits for differences in biomass. Vegetative traits showed higher plasticity and opposite genetic and plastic responses, masking the genetic component underlying field‐observed trait variation. Our study suggests that genetic differentiation may be inferred from observational data only for the traits most closely related to fitness.

Molecular characterization of bacteremic Escherichia coli isolates in Romania - Codruţa-Romaniţa Usein; Raluca Papagheorghe; Mihaela Oprea; Maria Condei; Monica Strãuţ (Folia Microbiologica, 2016)

Removal of Copper(II) from Aqueous Solutions by Biosorption-Flotation - Ligia Stoica; Ana-Maria Stanescu; Carolina Constantin; Ovidiu Oprea; Gabriela Bacioiu (Water, Air, & Soil Pollution, 2015)

Abstracts of Papers presented at a Workshop on Ecology of Botrytis and Sclerotinia and their Interaction With Other Microorganisms Abstracts of Papers Presented at a Workshop on Genetic Aspects ofFusarium oxysporum and Related Species Abstracts of Papers and Discussion Contributions Presented at the Dutch-Israeli (Diarp) Workshop on Environment-Friendly Crop Protection of the Flower Industry to Suit Future Market Trends - A. Ten Have; W. Oude Breuil; J. Wubben; W. Mulder; J. Visser; J. van Kan; T. Quidde; P. Tudzynski; T. M. O’Neill; G. De Meyer; K. Audenaert; J. Bigirimana; et al. (Phytoparasitica, 1999)